PENGARUH FAKTOR SITUASIONAL PANDEMI COVID-19 TERHADAP LOYALITAS KONSUMEN PADA E-GROCERY SHOPPING PLATFORM - Larasati, Oktavia; Raditha Dwi Vata Hapsari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of situational factors, in this case any of them induced by the Covid-19, on consumer loyalty. The effects to be proven are those of independent variables on the dependent variable, namely consumer loyalty. This study is categorized as quantitative research, which explains certain phenomena using numerical data, which in this study harvested through online questionnaires, in the analysis. The respondents are 170 people selected using purposive sampling method and non-probability sampling technique, a technique of sample determination using certain considerations. They are individuals who have the experience of buying consumer goods through online applications or platforms. The analysis performed in IBM SPSS Statistics version 16 program have resulted in that physical barriers have a significant and positive effect on consumer loyalty, store atmosphere has a significant and positive effect on consumer loyalty, mood has a significant and positive effect on consumer loyalty, and website quality has a significant and positive effect on consumer loyalty.